706 ETIOLOGICAL ROLE OF STRESS IN ACUTE CORONARY SYNDROME: THE STRESS-ACS-ACTION STUDY. (15th December 2022) - Magnani, Giuia; Denegri, Andrea; Bottioni, Federico; Gurgoglione, Filippo Luca; Tuttolomondo, Domenico; Noni, Manjola; Barocelli, Federico; Vrenozaj, Rosi; Catellani, Davide; Indrigo, Elia; Donelli, Davide; Maccari, Chiara; et al.
Abstract: Background: Acute coronary syndrome (ACS) is the main cause of mortality worldwide and despite the adherence to guidelines it is still burdened by an unacceptable risk for cardiovascular (CV) events recurrence, highlighting the need to identify other than traditional cardiovascular risk factors (CVrF) implicated in atherosclerotic plaque instability. In this regard, psychosocial stress appears to be a crucial player in the development of CV disease. Nevertheless, stress is not easy to standardize and the mechanisms by which it promotes coronary artery disease (CAD) are poorly understood. Materials and Methods: We therefore prospectively enrolled patients with ACS, stable coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) and subjects presenting traditional CVrF but without established CV disease. Multimodality cortisol assessment, expression of acute and chronic stress, through blood, urine and hair samples collection was ascertained at baseline. A regression analysis was performed to assess the relationships between significant variables at univariate analysis. Results: Fifty patients were enrolled in the present study. Cortisol levels in blood and urine were numerically higher in patients with ACS compared to CAD patients and subjects with traditional CVrF only. Hair cortisol levels did not differ between the three groups. The regression analysis showed an inverse correlation (R= -, 532, p<0.001 and R=-, 615, p<0.001 respectively) between urinary cortisol (UC) and UC/creatinine ratio and left ventricular ejection fraction (LVEF). Conclusion: The preliminary results of our study showed that patients with ACS did not have significantly higher levels of hair cortisol compared to stable patients. The finding of an inverse relationship between higher UC, UC/C ratio levels and lower LVEF values support a link between a hyperactivity of the hypothalamic-pituitary-adrenal axis and a worse ACS presentation. These preliminary data will be implemented with serial multimodality assessment of cortisol that allow potential implications in diagnosis and outcome.